Analisis Kualitas Pelayanan dan Suasana terhadap Loyalitas melalui Kepuasan Pelanggan di Kopi Bajawa Depok - Salika, Marselin Yapi; Surono, Surono (Indonesian Journal Publisher, 2024)
This study aims to analyze the effect of service quality and atmosphere on loyalty through customer satisfaction at Kopi Bajawa Depok. A total of 120 respondents were collected, consisting of customers who have visited at least twice. The research employs a quantitative method using primary data gathered from questionnaires. The sampling technique is Nonprobability Sampling, specifically Purposive Sampling. Data analysis was conducted using SmartPLS 3 software with the Structural Equation Model (SEM) approach. The results show that service quality significantly influences customer satisfaction and loyalty, but there is no significant effect of service quality on loyalty through customer satisfaction. Furthermore, atmosphere significantly affects customer satisfaction and loyalty but does not influence loyalty through customer satisfaction. Additionally, customer satisfaction does not have a significant effect on loyalty. These findings highlight the importance of maintaining high service quality and a pleasant atmosphere to enhance customer satisfaction and loyalty, especially in a competitive business environment. Future studies are recommended to explore additional variables that may further explain the relationship between customer satisfaction and loyalty at Kopi Bajawa Depok.